PENGECUALIAN PRAKTEK MONOPOLI YANG DILAKUKAN OLEH BUMN SESUAI PASAL 51 UU NO.5 TAHUN 1999 - MARSHIAS MEREAPUL GINTING; NINGRUM NATASYA SIRAIT; WINDHA WINDHA (Universitas Sumatera Utara, 2013)
After the entry into force of Law no. 5 of 1999, the monopolistic practices in the Indonesian economic activity expressly prohibited by law, but there are exceptions to the state, which in the presence of Law No.5 of 1999 clause 51, have legal legitimacy to claim exemption in monopolistic practices in Indonesia. Which are expected to given to state-owned monopoly, it can help the implementation of the 1945 Constitution Clause 33 of the Indonesian economy. Issues raised in this paper are as follows: how the regulation of monopolies in the legislation in Indonesia, how the position of BUMN in the economy in Indonesia as businesses that are entitled to monopolistic practices in Indonesia economy and how the exemption against monopolistic practices by BUMN. This research was conducted with the juridical-normative, remember to be studied is the provision of an article and its application in practice. Data obtained from examining the legislation and literature associated with the formulation of the problem. Monopoly by the state under the provisions of Clause 51 of Law 5 of 1999 is that monopoly or concentration of activity that can be done only over the branches of production that dominate the lives of many people and that is important for the country. Because until now there is no certainty in legislation which imposes limits is